Utilization of whey in bakery products-A Review - Paul, S; S Kulkarni; RN Chauhan (Indian Journal of Dairy Science, 2022)
Whey is a vast repository of valuable nutrients and serves as a key ingredient in the bakery sector. Whey being a significant by product of the dairy industry is necessary to be utilized to reduce the burden of its disposal on the environment, which is attributed to the high BOD of whey. Whey based ingredients find an ocean of application in foods. Whey based ingredients have superior functional properties attributable to whey proteins which results in enhancement of textural and chemical properties of products they are applied in. Whey proteins are used as fat replacers, emulsifiers, flavour and appearance enhancers etc in a wide category of bakery products. Whey based ingredients can negate the use of dough conditioners due to high water binding capacity which aids in developing improved texture and fine even crumb. Whey ingredients can boost levels of protein, calcium, potassium and other minerals in bakery products. With increasing demand for clean label products and low fat products with the same textural attributes as full fat ones the demand for whey ingredients is surging. In this article we review the applications of whey based ingredients in bakery products.